Numerical study on clogging mechanism of slurry infiltration in porous media based on coupled CFD-DEM method. (October 2022) - Lin, Yufeng; Fang, Yong; He, Chuan
Highlights: A coupled CFD-DEM model of the slurry infiltration is proposed. Internal structure of porous media can be depicted by single particle. Evolution from local clog to overall clog is a process from point to surface. Study of slurry penetration can be divided into local clog and overall clog. Large pores in the ground determine the effect of slurry support in shields. Abstract: The clogging behavior of particles is a ubiquitous phenomenon. In slurry support, the clogging behavior of slurry particles is expected to occur rapidly, but the microscopic mechanism is not well understood at present. The common penetration column test can only analyze some macroscopic parameters; it cannot track the movement of particles. In order to investigate the clogging mechanism and migration of slurry particles, a coupled CFD-DEM model of the penetration column test is employed in this paper. Based on a previous experimental study (Lin et al., 2021 ), the numerical model was appropriately simplified. The simulation results indicate that the apertures of homogeneous porous media have a minimum value; particles bigger than this value will be trapped and particles smaller than this value will escape. Furthermore, there is a maximum value; particles smaller than this value have the chance to enter the ground. Smaller particles always have longer trails than bigger ones before being captured. Pores of different sizes are distributed according to a certain rule in porous media, which leads to dispersed local clogs at the beginning of the infiltration. When large pores are blocked, local clogs will converge to the overall clog on a plane (i.e., filter cake). The simulation in this paper reveals the evolution process from local clog to overall clog, which can be summarized as a process from point (local clog) to surface (overall clog). This indicates that future models can focus on a pore rather than the entire ground, which could greatly reduce computational effort and leave more space to simulate more and smaller particles. This study provides a new insight for slurry infiltration and offers a reference for other similar investigations.